Translation of Antonio Machado’s Poetry into Ukrainian - Kovalenko, A. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
Kovalenko A. Translation of Antonio Machado’s Poetry into Ukrainian